PENGABDIAN KEPADA MASYARAKAT DALAM PENGELOLAAN DAN PEMILIHAN SAMPAH DI BATU AJI BATAM - Arsyad Sumantika; Ganda Sirait; Bahariandi Aji Prasetyo; Elsya Paskaria Lodya Tarigan (PUAN INDONESIA, 2026)
This community service program was implemented with the main objective of implementing an effective and sustainable waste management and sorting system in Batam City. The methods used in implementing this program include a participatory approach through a series of focus group discussions, waste sorting training, and the establishment of a community-based waste management system in the pilot village, namely Batu Aji Village. As demonstrated by the fact that the majority of residents are now actively sorting waste at the household level, the primary outcomes of this community service program demonstrate a notable improvement in community awareness and waste sorting skills. The amount of mixed garbage in the intervention region has decreased because to the organic-inorganic sorting system's adoption, which has also helped to lower the amount of waste that ends up in landfills. The community's economy benefits from this scheme as well, as waste banks and recycling initiatives generate more revenue. Keywords— Waste Management, Sorting, Community, Batam